2013
DOI: 10.1007/s13277-013-1168-2
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of elevated ezrin in patients with osteosarcoma

Abstract: Published studies researching the prognostic significance of ezrin expression in patients with osteosarcoma are inconclusive and heterogeneous. We conducted a meta-analysis to assess its prognostic value more precisely. The hazard ratios with corresponding 95 % confidence intervals were calculated to evaluate the effects. Five studies with 318 osteosarcoma patients were included to estimate the relationship between ezrin and disease-free survival, and ezrin and overall survival. Compared with osteosarcoma pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Interestingly, alterations in a few other candidate genes, such as p53 (Fu et al 2013), ezrin (Lun et al 2014) and vascular endothelial growth factor (Qu et al 2012), have also been proposed as potential prognostic makers for osteosarcoma other than the RB1 gene we reported here. Interestingly, alterations in a few other candidate genes, such as p53 (Fu et al 2013), ezrin (Lun et al 2014) and vascular endothelial growth factor (Qu et al 2012), have also been proposed as potential prognostic makers for osteosarcoma other than the RB1 gene we reported here.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Interestingly, alterations in a few other candidate genes, such as p53 (Fu et al 2013), ezrin (Lun et al 2014) and vascular endothelial growth factor (Qu et al 2012), have also been proposed as potential prognostic makers for osteosarcoma other than the RB1 gene we reported here. Interestingly, alterations in a few other candidate genes, such as p53 (Fu et al 2013), ezrin (Lun et al 2014) and vascular endothelial growth factor (Qu et al 2012), have also been proposed as potential prognostic makers for osteosarcoma other than the RB1 gene we reported here.…”
Section: Discussionsupporting
confidence: 50%
“…Substantial efforts have been made to search for novel molecular markers to guide the management and improve the prognosis of osteosarcoma patients in recent years. Interestingly, alterations in a few other candidate genes, such as p53 (Fu et al 2013), ezrin (Lun et al 2014) and vascular endothelial growth factor (Qu et al 2012), have also been proposed as potential prognostic makers for osteosarcoma other than the RB1 gene we reported here. It is worth noting that the prognostic values of these candidate genes have been investigated individually in the majority of studies.…”
Section: Discussionsupporting
confidence: 50%
“…Similar results were presented by Xu-Dong et al [26], who revealed that the high mRNA level of ezrin gene was related to shorter lungmetastasis-free and overall survival time of patients with osteosarcoma. Lastly, two independent meta-analyses by Wang et al [32] and Lun et al [33], both including five studies of 318 patients with osteosarcoma, showed that overall survival was significantly lower in patients with osteosarcoma with high ezrin expression at biopsy.…”
Section: Discussionmentioning
confidence: 98%
“…Rho or Akt signaling pathways regulate the phosphorylation of ezrin to inhibit apoptosis and promote cellular proliferation. Meta‐analysis has shown that ezrin expression is significantly upregulated in osteosarcoma tissues and correlates negatively with five‐year survival rate. However, the role of ezrin in osteosarcoma has not been studied.…”
Section: Introductionmentioning
confidence: 99%